Analysis Of The Effect Of Foreword Performance On The Quality Of Construction Projects In Tarakan City - eko prihartanto; Iif Ahmad Syarif; Edy Utomo (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
Tarakan City is a developing city for development where the city has undergone many developments so that it requires quality human resources in managing development. If human resources are able to manage development with good quality, it can be said to be successful in the development process. To improve the quality of a construction project, it is necessary to pay attention to the determination of workers with good quality, therefore before starting the construction of a construction project it is necessary to make a selection made by the contractor of the foremen workers which is important so that the foremen selected have good quality. So far, the discussion in Tarakan City is not yet known how the foreman's performance affects the quality of construction project work in Tarakan City.In this study, the type of research used is quantitative research using a Likert scale. Place and time of research in the Project for Improving the Quality of Slums in the Karang Rejo Area of Tarakan City. The data used is the foreman's performance data on construction projects in Tarakan City with the foreman's performance aspects seen are work ability, participation, work facilitation, bias, providing examples of experience on the quality of construction projects in Tarakan City. Supporting data from the internet, books and so on.The results obtained from this study are the indicators that most influence the quality of construction work in Tarakan City, namely the foreman's ability to read and understand working drawings, being able and skilled in doing his work, being able to organize materials. well and able to organize the tools well. able to solve problems that occur in the field.